Career Orientation, Work-Life Balance, and Resilience on Leather Footwear MSME Performance - Yudi Wahyudin Suwandi; Imas Komariyah; Asep Ghofir Ali; Resty Ismawanti; Vidya Ramadhan Putra Pratama (International Journal of Accounting and Finance in Asia Pasific (IJAFAP), 2026)
Micro, Small, and Medium Enterprises (MSMEs), particularly in the leather footwear sector, face competitive challenges that require strengthening human resources as a key factor of performance. This study aims to analyze the effects of career orientation, work-life balance, and resilience on MSME performance. The research employed a quantitative approach with a cross-sectional design through a survey of 153 MSME owners using a Likert-scale questionnaire. Data were analyzed using multiple linear regression supported by validity, reliability, and classical assumption tests. The results show that career orientation (b = 0.276, p 0.001), work-life balance (b = 0.183, p = 0.016), and resilience (b = 0.451, p 0.001) positively and significantly influence MSME performance, with resilience emerging as the strongest predictor. Furthermore, the model explains 61.1% of the variance in MSME performance (R² = 0.611). These findings indicate that psychological resources play an important role in improving MSME performance in a dynamic environment. This study extends the Resource-Based View (RBV) perspective by emphasizing the importance of intangible assets as a source of competitive advantage, particularly in the creative leather footwear industry.